Pengaruh Latar Belakang Pendidikan dan Skala Usaha terhadap Penggunaan Informasi Akuntansi pada UMKM Sektor Kuliner Se-Kota Tegal (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to determine the influence of educational background and business scale on the use of accounting information among culinary Micro, Small, and Medium Enterprises (MSMEs) in Tegal City. The research is motivated by the fact that accounting information plays a crucial role in business decision-making, particularly in financial planning, cost control, and profit measurement. However, many MSME actors still underutilize this information, which may hinder their ability to achieve sustainable growth. The study employed a quantitative method with a survey approach. The population consisted of culinary MSME actors in Tegal City, and data were collected from 97 respondents through the distribution of structured questionnaires. Data analysis was carried out using multiple regression to test the partial and simultaneous effects of the independent variables. The results indicate that both educational background and business scale have a partial and significant effect on the use of accounting information. Specifically, the t-value for educational background is 6.360 and for business scale is 4.519, both greater than the t-table value of 1.98525, with a significance level of < 0.001. Simultaneously, the F-value is 32.870, which is greater than the F-table value of 3.0902, with a significance level of < 0.001. These findings confirm that the regression model is statistically significant. In conclusion, educational background and business scale are important determinants that encourage the use of accounting information among culinary MSMEs in Tegal City. The study highlights the need for training programs, workshops, and policy support to enhance MSME actors’ understanding of accounting practices, thereby strengthening their decision-making capacity and long-term competitiveness.